2001
DOI: 10.1093/embo-reports/kve168
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways contribute to nuclear import of core histones

Abstract: Nuclear import of the four core histones H2A, H2B, H3 and H4 is one of the main nuclear import activities during S-phase of the cell cycle. However, the molecular machinery facilitating nuclear import of core histones has not been elucidated. Here, we investigated the pathways by which histone import can occur. First, we show that core histone import can be competed by the BIB (β-like import receptor binding) domain of ribosomal protein L23a suggesting that histone import is an importin mediated process. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
161
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(176 citation statements)
references
References 23 publications
9
161
2
1
Order By: Relevance
“…Nucleolar staining may be due to a vast excess of H1°histones after import into the nuclei of the permeabilized cells, where they may bind to ectopic sites in the nucleus, perhaps as basic proteins to the ribosomal RNA accessible in the nucleolus. This nucleolar staining has been observed previously also with other proteins, for instance with core histones (10,25) and the parathyroid hormone-related protein (33).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Nucleolar staining may be due to a vast excess of H1°histones after import into the nuclei of the permeabilized cells, where they may bind to ectopic sites in the nucleus, perhaps as basic proteins to the ribosomal RNA accessible in the nucleolus. This nucleolar staining has been observed previously also with other proteins, for instance with core histones (10,25) and the parathyroid hormone-related protein (33).…”
Section: Resultssupporting
confidence: 82%
“…Unlike H1 import, core histones are imported by at least five different importins, and either Imp␤ or Imp7 is capable of targeting the core histone into the nuclei of permeabilized cells on their own. Cooperativity of both importins has neither been demonstrated in binding studies nor in the in vitro import of core histones (24,25). This indicates that core histones are imported by a monomeric import receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coregulation of import could ensure that similar amounts of specific proteins are imported at the same time or delivered to the same place in the nucleus. To add to the complexity of determining which Kap imports a particular cargo, it has been shown that several proteins can be imported into the nucleus by more than one Kap (Rout et al, 1997;Jakel and Gorlich, 1998;Pemberton et al, 1999;Mosammaparast et al, 2001Mosammaparast et al, , 2002bMuhlhausser et al, 2001). Indeed many essential yeast nuclear proteins appear to have more than one route into the nucleus, with the preferred route being mediated by a nonessential karyopherin (Rout et al, 1997;Pemberton et al, 1999;Mosammaparast et al, 2001Mosammaparast et al, , 2002b It has been previously shown that the TATA-binding protein is imported by the karyopherin Kap114p (Morehouse et al., 1999;Pemberton et al, 1999).…”
mentioning
confidence: 99%